IMPROVING VOCABULARY MASTERY BY USING SONGS ( A CLASSROOM ACTION RESEARCH IN THE SEVENTH YEAR OF SMPN 1 SIDOHARJO SRAGEN IN THE 2009/2010 ACADEMIC YEAR ) - YANTO, DWI ANTON TIMUR (2011)
This research aims at describing the implementation of vocabulary mastery by using songs in teaching English, and describing the improvement of student vocabulary mastery in the seventh year students of SMP Negeri 1 Sidoharjo Sragen in the 2009-2010 academic year. The research paper is an action research in which the data are in the form of field note, interview script, and students' worksheet. The research was done on March until June 2010. The researcher took 35 students as the object. The researcher gets the data from events, informants, and document. While the techniques of collecting data are observation, interview, and document. After collecting the data and analysing the action by using Action Research procedure, the writer described the result of the research. The tests were given after the implementation of the action of each cycle (post-tests). The test consisted of twenty items. In the first cycle, he found that there were 22 students who got the score more then 65. It means that score achievement was 62,8. Meanwhile, the students' achievement of the post-test 2 was better then pre-test and post-test 1, the students who got the score more than 65 in the second cycle were 26 students, the score achievement was 74. From the two tests the writer compares to know how far the students can achieve the target vocabulary by using songs. Finally, the writer concludes that by using songs the students can achieve the target vocabulary well. After knowing the procedures and the result, writer presents the strengths and weaknesses of teaching vocabulry using songs. The strengths are: (a) The students are more interested in attending the class, (b) The students are trained to think quickly and automatically (c) The students are motivated to be active in the class (d) singing is happy and stress-free activity and to a positive classroom. The weaknesses are (a) the teacher must be skilful and master the target language perfectly (b) the teacher must spend her spere time at home to buy and prepare the suitable materials. The conclusion is teaching vocabulary using songs in SMP N 1 Sidoharjo Sragen was good. The use of teaching aids in Action Research is very appropriate and helpfull in teaching learning process.